The Effect of a New Denture Adhesive on Bite Force Until Denture Dislodgement - Mutlu ¨Ozcan, DMD, PhD;1 Jeroen M. van der Sleen, DDS;2 Hemmo Kurunm¨aki, (Journal of Prosthodontics, 2005)
Denture adhesives are used to improve the denture retention and comfort of complete denture wearers.